2018
DOI: 10.1080/07448481.2018.1432624
|View full text |Cite
|
Sign up to set email alerts
|

Sexual misconduct policies and administrator perceptions among 4-year colleges and universities in Georgia

Abstract: There is extensive variability in institutional responses to sexual violence across universities and colleges despite recent media attention and federal guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Changes in 2011 to Title IX of the Education Amendments (Title IX) required colleges to make efforts to prevent campus sexual violence (Larkin, 2016). A few studies that investigated the impact of these recent Title IX updates (n = 4) indicated that these changes have shed light on and sought to fill gaps in university policies regarding sexual assault and sexual harassment (Bellis et al, 2018;Miller, 2018). These changes are thought to have increased student empowerment to report victimisation experiences (Miller, 2018), potentially increasing access to supportive services, including contraceptive care, following victimisation.…”
Section: Title IX Of the Education Amendmentsmentioning
confidence: 99%
“…Changes in 2011 to Title IX of the Education Amendments (Title IX) required colleges to make efforts to prevent campus sexual violence (Larkin, 2016). A few studies that investigated the impact of these recent Title IX updates (n = 4) indicated that these changes have shed light on and sought to fill gaps in university policies regarding sexual assault and sexual harassment (Bellis et al, 2018;Miller, 2018). These changes are thought to have increased student empowerment to report victimisation experiences (Miller, 2018), potentially increasing access to supportive services, including contraceptive care, following victimisation.…”
Section: Title IX Of the Education Amendmentsmentioning
confidence: 99%
“…Emerging research on how administrators perceive the institutional response to sexual assault finds a somewhat more positive outlook. In a state-wide, multi-phase study of administrators in the U.S. state of Georgia, almost 30% of participants stated that their response could be a model for other institutions (Bellis et al, 2018). Moylan et al (2020) also found that campus personnel report improvements in response efforts and an increased focus on fairness.…”
Section: Campus Personnel Perceptions Of Institutional Responsementioning
confidence: 99%
“…With few exceptions, there is little research on best ways to engage with students with campus policy information (Potter et al, 2016). Although effective campus SV policies are needed, the development of such is often a time-and labor-intensive process requiring IHE investment, implementation and compliance are often problematic, and outcomes are long-term (Backman et al, 2020;Bellis et al, 2018). Accordingly, it is important to shift the focus from campus-level policies to state-and national-level policies that can collectively work to prevent campus SV.…”
Section: Policy Levelmentioning
confidence: 99%